2019
DOI: 10.18203/2320-6012.ijrms20194291
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and practices of ASHA workers related to maternal-child health and their performance affecting factors: A mixed method study in Deganga block, North 24 parganas district, West Bengal, India

Abstract: Background: ASHA acts as a ‘bridge’ between the rural people and health service outlets and plays a central role in achieving national health and population policy goal. ASHAs form the backbone of the NRHM. They need to provide preventive, promotive and curative health facilities in the rural community. Maternal and child health is an important public health issue which indicates level of socio-economic development in each and every country. ASHA workers are the main front-line workers in primary health care d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
5
5
2
Order By: Relevance
“…None of ASHA workers in urban area and 4.3% ASHA workers working in rural areas was having adequate knowledge regarding detection of danger signs of new-born. In contrary to our findings Pal J et al 6 found that majority of ASHA workers (80.53%) had correct knowledge regarding danger sign of new-born. In the present study, majority of ASHA workers (94.3% in rural and 93.3% in urban areas) had adequate knowledge regarding cord stamp care.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…None of ASHA workers in urban area and 4.3% ASHA workers working in rural areas was having adequate knowledge regarding detection of danger signs of new-born. In contrary to our findings Pal J et al 6 found that majority of ASHA workers (80.53%) had correct knowledge regarding danger sign of new-born. In the present study, majority of ASHA workers (94.3% in rural and 93.3% in urban areas) had adequate knowledge regarding cord stamp care.…”
Section: Discussioncontrasting
confidence: 99%
“…In the Present study, majority of ASHA workers (95.7.1% in rural and 80% in urban areas) had adequate knowledge of routine immunization schedule. Similar finding was seen in a study conducted by Saxena S et al 10 Lower percentages, 86.32%, 78.0% and 60% were observed by Pal J et al, 6 Sugandha BK et al 4 and Kori S et al 13 respectively in their study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Fatima et al [ 5 ] observed 60% of beneficiaries motivated for institutional delivery by ASHA workers and 96% beneficiaries escorted for institutional delivery by ASHA workers. A study conducted by Pal et al [ 14 ] showed almost similar results to the present study that about 60.53% deliveries were escorted by ASHA workers.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, it claims that the welfare of mother and child is a vital public health issue that reflects each nation's socioeconomic standing. ANMs, ASHA workers, and AWWs are among the frontline staff in the primary healthcare delivery system who are expected to work in this area to enhance reproductive and child health (RCH) indicators [ 14 ].…”
Section: Reviewmentioning
confidence: 99%